Python Programming A modular approach - Naveen, Kumar; Naveen, Kumar (Pearson Education India, 2017)
"Python Programming introduces one of the most rapidly evolving and preferred programming language using the concept of modularity. One of the highlights of the text is its in-depth treatment of basic concepts.